2016
DOI: 10.5603/fm.a2015.0076
|View full text |Cite
|
Sign up to set email alerts
|

Does allicin combined with vitamin B-complex have superior potentials than alpha-tocopherol alone in ameliorating lead acetate-induced Purkinje cell alterations in rats? An immunohistochemical and ultrastructural study

Abstract: (Folia Morphol 2016; 75, 1: 76-86)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…Additionally, degenerating pyknotic cells and vacuolation in the Purkinje cell layer were easily detected in the Pb group. Similarly, previous studies reported that Pb exposure during cerebellar development significantly decreased the number of Purkinje cells and ascorbic acid treatment mitigated Pb-induced impairments in the PA group [17,20,34,35,36]. Our results are consistently similar with previous studies, which observed that ascorbic acid prevents the harmful effects of other heavy metals including mercury and cadmium on brain development [37,38].…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, degenerating pyknotic cells and vacuolation in the Purkinje cell layer were easily detected in the Pb group. Similarly, previous studies reported that Pb exposure during cerebellar development significantly decreased the number of Purkinje cells and ascorbic acid treatment mitigated Pb-induced impairments in the PA group [17,20,34,35,36]. Our results are consistently similar with previous studies, which observed that ascorbic acid prevents the harmful effects of other heavy metals including mercury and cadmium on brain development [37,38].…”
Section: Discussionsupporting
confidence: 92%
“…For this reason, the cerebellum is especially vulnerable to developmental damages on exposure to oxidative stress [12,20,23,28,42]. reactive oxygen species in the CNS [33]. Another study described that allicin alters the GFAP content in various brain regions and has a principal neuroprotective influence in minimising neuroglia injury in the CNS [9]; in such a basis, the usage of garlic in the current study diminished GFAP expression in rats' cerebellum.…”
Section: Discussionmentioning
confidence: 51%
“…GFAP positive cells appeared brown and nuclei appeared blue. The positive results were indicated by brown coloration of the cell membrane and cytoplasm of the astrocytes [33]. Finally, all slides were examined with an Olympus BX53 microscope equipped with camera (Olympus, Tokyo, Japan) at different magnifications.…”
Section: Histological and Immunohistochemical Methodsmentioning
confidence: 99%
“…Group II (LA treated group) (positive control [PC]) was given 10 mg/kg of LA, orally for 30 days [24,25]. Group III (NS treated group) was given 200 mg/kg BW of NS water suspension, orally for 30 days [26,27], while Group IV (NS followed by LA treated group) was pre-treated with NS 200 mg/kg BW, orally for 30 days [13], followed by LA 10 mg/kg BW daily for another 30 days [24,25]. …”
Section: Methodsmentioning
confidence: 99%